Technological Possibilities for Agricultural Growth and Stability in Western Rajasthan: An Assessment - Mruthyunjaya, Mruthyunjaya; Malhotra, S P; Sen, Amal Kumar (Annals of Arid Zone, 2016)
Agriculture in western Rajasthan is not only backward but also highly unstable. Lots of money being spent by Government on famine relief over years have neither strengthened the production base of the economy nor enabled it 10 mitigate the rigours imposed by recurring droughts and famines. The problems and prospects of the application of arid zone technologies as a permanent solution to the arid zone problems is assessed. More of food, fodder and fuel can be produced. Adequate employment is also possible. However, it is shown that application of technologies needs pooling of State, National and'even International resources.